Successful treatment of a patient with severe thallium poisoning in a coma using Prussian blue and plasma exchange: A case report. Issue 8 (February 2019) - Lin, Guodong; Yuan, Luo; Bai, Lili; Liu, Yanqing; Wang, Yongan; Qiu, Zewu
Abstract: Rationale: This is the first reported severe thallium poisoning patient successfully treated with Prussian blue (PB) and plasma exchange (PE). Patient concerns: A 42-year-old woman in a coma owing to severe thallium poisoning was admitted to our department after day 44 of poisoning. At admission, blood and urine thallium concentrations were 380.0 and 2580.0 ng/mL, respectively. Diagnosis: The patient was diagnosed with toxic encephalopathy induced by thallium poisoning; in addition, she was also diagnosed with bilateral pneumonia, respiratory failure, moderate anemia, hypoproteinemia, and electrolyte imbalance based on her chest X-ray, blood gas analysis, Hb level, albumin levels, and serum electrolyte results. Interventions: The patient was intubated and treated with PB (6600 mg/d, 15 days in total) combined with PE (once daily, 5 days in total) as well as other symptomatic supportive care measures. Outcomes: After treatments, her blood and urinary thallium concentrations gradually decreased and on the 13th day after admission, the blood thallium concentration decreased to 0 ng/mL. The oxygenation index gradually improved, meantime, the patient gradually regained consciousness, and on the 50th day of admission, the patient's consciousness reverted to a clear-headed state. The patient recovered mostly after 37 months of follow-up. Lessons: Through this case, we learned that the gradual reduction in blood and urine thallium concentration and the patient's improved condition is correlated with PB and PE treatment. For patients with severe thallium poisoning, this treatment method might be effective; but the exact curative effect is unconfirmed, requiring further research to verify. Abstract : Supplemental Digital Content is available in the text